Impact of the COVID‐19 pandemic on the in‐hospital diagnostic pathway of breast and colorectal cancer in the Netherlands: A population‐based study - Wouter Wolfkamp; Joyce Meijer; Jolanda C. vanHoeve; Felice vanErning; Lioe‐Fee deGeus‐Oei; Ignace deHingh; Jeroen Veltman; Sabine Siesling; the COVID and Cancer‐NL Consortium (Cancer Medicine, 2024)
Abstract Background In the Netherlands, the COVID‐19 pandemic resulted in a temporary halt of population screening for cancer and limited hospital capacity for non‐COVID care. We aimed to investigate the impact of the pandemic on the in‐hospital diagnostic pathway of breast cancer (BC) and colorectal cancer (CRC). Methods 71,159 BC and 48,900 CRC patients were selected from the Netherlands Cancer Registry. Patients, diagnosed between January 2020 and July 2021, were divided into six periods and compared to the average of patients diagnosed in the same periods in 2017–2019. Diagnostic procedures performed were analysed using logistic regression. Lead time of the diagnostic pathway was analysed using Cox regression. Analyses were stratified for cancer type and corrected for age, sex (only CRC), stage and region. Results For BC, less mammograms were performed during the first recovery period in 2020. More PET‐CTs were performed during the first peak, first recovery and third peak period. For CRC, less ultrasounds and more CT scans and MRIs were performed during the first peak. Lead time decreased the most during the first peak by 2 days (BC) and 8 days (CRC). Significantly fewer patients, mainly in lower stages, were diagnosed with BC (−47%) and CRC (−36%) during the first peak. Conclusion Significant impact of the COVID‐19 pandemic was found on the diagnostic pathway, mainly during the first peak. In 2021, care returned to the same standards as before the pandemic. Long‐term effects on patient outcomes are not known yet and will be the subject of future research.